An Impact Analysis of Eco-friendly Agricultural Practices in Paddy - A. Janaki Rani,; H. Philip,; P.P. Murugan, (Journal of Agricultural Extension Management, 2025)
During the last four decades, spectacular progress has been achieved in agricultural production in the country. As compared with 51 million tonnes of food grain production in 1950-51 , India achieved food grain production of 211.17 million tonnes during 2001-02, making it not only se lf sufficient in food production but also in a buffer stock of over 30 million tonnes. This achievement was because of high intensity cropping and cultivation of high yielding varieties that were highly input responsive. Farmers used chemicals and synthetic pesticides, fertilizers and. growth promoters above the level of the recommended dose with a motive to get higher yields. In this process the soil, water and environment got polluted besides degradation of natural resources